Обнаружение тупоконечных волосков антеннального флагеллума самок комара Anopheles claviger (Diptera, Culicidae) - Смолина, Н.А. (Вестник зоологии, 1980)
The scanning electron-microscopy description of the short blunt-shaped chemoreceptors on the antennal flagellum of the Anopheles claviger Mg. female is presented.